A roda em movimento e os movimentos da roda: refletindo sobre experiências - Torres, Ana Elídia; Pasquini, Janaína; Santos, Liamar Aparecida dos [UNESP]; Yasui, Silvio [UNESP] (My University, 2012)
This article aims to narrate and analyze possibilities on aspects of the work developed by the group that composes the Mental Health and Public Health Improvement, using the Wheel Method, created by Gastão W. Campos, in different and diverse articulations and work organization spaces in psychosocial care field, such as Mental Health Forum, work groups related to Regional Collegiate Management (CGRs), with municipal teams to organize mental health network and with newcomer residents to a therapeutic residence It is from these different experiences that it is intended to reflect, discuss and promote a dialogue on the possibilities of the Wheel Method.

O presente artigo tem por objetivo narrar e analisar aspectos do trabalho desenvolvido pelo grupo que compõe o Aprimoramento de Saúde Mental e Saúde Coletiva, na utilização do Método da Roda, criado por Gastão W. Campos, em diferentes e diversos espaços de articulação e organização do trabalho no campo da atenção psicossocial, tais como o Fórum de Saúde Mental, grupos de trabalho ligados aos Colegiados de Gestão Regional (CGRs), com equipes municipais para organização da rede de saúde mental e com moradores recém-chegados a uma residência terapêutica. É a partir dessas diferentes experiências que se pretende refletir, problematizar e promover um diálogo sobre as possibilidades do Método da Roda.
Wheel-in-movement and the movements of the wheel: reflecting upon experiences
Keywords: Wheel method; Psychosocial attention; Public health; Network; Método da roda; Atenção psicossocial; Saúde coletiva; Rede